From fundamentals to financial assets: the evolution of understanding price formation in the EU ETS - Marina Friedrich; Eva-Maria Mauer; Michael Pahle; Oliver Tietjen (ZBW - Leibniz Information Centre for Economics, 2020)
Price formation in the EU Emission Trading System (EU ETS) has persistently puzzled economists and policy makers. In recent years, the empirical literature investigating this topic has expanded considerably, but a synthesis of what could be learned about price formation as a whole including the last wave of research is still missing. To fill this gap, we review the empirical literature structured along three categories of price drivers and related econometric methods. For better guidance of the reader, we draw on a simple theoretical model of price formation that we subsequently extend to connect the three different strands of literature: demand-side fundamentals, regulatory intervention and finance. In particular the insights from the second and third strand challenge the widespread view that allowance markets primarily reflect marginal abatement costs. Accordingly, the next wave of research should focus on shedding light on the complex interplay of compliance, regulatory uncertainty and financial trading motives.
Keywords: Q48; Q50; Q56; Q58; 330; emission trading; EU ETS; price formation; literature review